2007
DOI: 10.1200/jco.2007.25.18_suppl.7507
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of axitinib (AG-013736; AG) in patients (pts) with advanced non-small cell lung cancer (NSCLC): A phase II trial

Abstract: 7507 Background: A correlation between vascular endothelial growth factor (VEGF), microvessel density, and prognosis has been reported in pts with NSCLC. AG is a small molecule inhibitor of the receptor tyrosine kinases, with picomolar potency against VEGFR 1, 2 and 3 and nanomolar potency against PDGFR-β and KIT. This is an open-label, multicenter phase II study examining the efficacy and safety of AG in pts with advanced NSCLC. Methods: Pts with stage IIIB or metastatic NSCLC received AG 5 mg BID. Eligibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Axitinib was used during the synthesis of CFI-400437, as a model of a potent PLK4i [60]. In 2012, axitinib was approved by the FDA for use in renal cell carcinoma [57,68,69] and has since been in clinical trials to treat thyroid [70] and advanced non-small cell lung [71] cancer as well as melanoma [61,72].…”
Section: Introductionmentioning
confidence: 99%
“…Axitinib was used during the synthesis of CFI-400437, as a model of a potent PLK4i [60]. In 2012, axitinib was approved by the FDA for use in renal cell carcinoma [57,68,69] and has since been in clinical trials to treat thyroid [70] and advanced non-small cell lung [71] cancer as well as melanoma [61,72].…”
Section: Introductionmentioning
confidence: 99%
“…The median duration of response was 9.4 months. The median survival was 12.8 months (95% CI, 9.9 to undefined), and progression-free survival was 5.8 months (95% CI, 3.8 to 10.2 months) [ 140 ].…”
Section: Introductionmentioning
confidence: 99%
“…Axitinib (AG-013736) is an oral, potent, and selective inhibitor of vascular endothelial growth factor receptors 1, 2, 3 [ 1 ]. Early clinical trial experience in over 500 cancer patients has demonstrated that it has activity and is well-tolerated as a single agent [ 2 4 ] and in combination with various chemotherapeutic regimens [ 5 , 6 ]. Axitinib is currently in phase III development for advanced renal cell carcinoma and in phase II development for various other tumor types.…”
Section: Introductionmentioning
confidence: 99%